The Inflation–Output Nexus: Empirical Evidence from Pakistan, Indonesia and Iran - Rasul, Saira; Khan, Himayatullah; Ali Bhatti, Arshad (The Journal of Humanities & Social Sciences, 2023)
This paper observes the dynamic associations among inflation, output growth for Pakistan, Indonesia and Iran with their uncertainties. We use various GARCH models to estimate the conditional variances that are used as proxies for creating uncertainties of output growth and inflation. Finally, we use bi-variate ARMA (p,q)-GARCH-M (1,1) models with diagonal BEKK specification to find the twelve causal relationships between inflation, its uncertainty vs output growth with its uncertainty. Our evidence supports numeral of important conclusions. Firstly, we find that Friedman (1977) hypothesis, i.e., inflation clues to increase the uncertainty of inflation, which is not supported in both Pakistan and Iran but not for Indonesia. Secondly, Cukierman-Meltzer (1986) hypothesis is accepted in Pakistan and Holland (1995) hypothesis is accepted in Indonesia and Iran. Thirdly, Black (1987) hypothesis is accepted in Pakistan and Iran whereas, Deveraux (1989) hypothesis is accepted in Indonesia. We also discover that higher output growth causes to reduce the inflation in both Pakistan plus Indonesia. Higher inflation reduces output growth in both Pakistan and Indonesia but not in Iran. We also conclude that the policy makers of these countries may take measures to reduce inflation rate because output growth is inversely linked with inflation and the prevailing uncertainty in the economy.